Structural and biochemical insights into the allosteric activation mechanism of AMP‐activated protein kinase. (9th December 2016) - Li, Jin; Li, Shuying; Wang, Fengzhong; Xin, Fengjiao
Abstract : The AMP‐activated protein kinase (AMPK), a complicated αβγ heterotrimer, can sense cellular energy status and maintain energy homeostasis via switching catabolic and anabolic pathways. AMPK also participates in the regulation of many other life activities, including the cell cycle, cell polarity, autophagy, and life span. Therefore, AMPK is widely studied as a potential drug target for treatment of type 2 diabetes and some other metabolic diseases, cancers, and cardiovascular diseases. Similar to other kinases, the phosphorylation of α‐Thr172 in the activation loop by upstream kinases is crucial for the activation of AMPK. In addition, the binding of AMP and its analogues to the γ subunit causes further allosteric activation, which makes AMPK distinctive from other kinases. Here, we give a brief introduction to the domain constitutions of mammalian AMPK and then systematically review its allosteric activation mechanism from a structural and biochemical view. Abstract : AMP‐activated protein kinase (AMPK) is widely studied as a potential drug target for treatment of type 2 diabetes (T2D), cancers, and cardiovascular diseases. Its phosphorylation in α‐Thr172 by upstream kinases is crucial for basal activity and AMP, and its analogues binding to γ subunit causes further allosteric activation. The review summarizes the domain constitutions of mammalian AMPK and then systematically describes its allosteric activation mechanism from a structural and biochemical view.